Mutation dynamics of CpG dinucleotides during a recent event of vertebrate diversification - Fábio Pértille; Vinicius H. Da Silva; Anna M. Johansson; Tom Lindström; Dominic Wright; Luiz L. Coutinho; Per Jensen; Carlos Guerrero-Bosagna (Epigenetics, 2019)
DNA methylation in CpGs dinucleotides is associated with high mutability and disappearance of CpG sites during evolution. Although the high mutability of CpGs is thought to be relevant for vertebrate evolution, very little is known on the role of CpG-related mutations in the genomic diversification of vertebrates. Our study analysed genetic differences in chickens, between Red Junglefowl (RJF; the living closest relative to the ancestor of domesticated chickens) and domesticated breeds, to identify genomic dynamics that have occurred during the process of their domestication, focusing particularly on CpG-related mutations. Single nucleotide polymorphisms (SNPs) and copy number variations (CNVs) between RJF and these domesticated breeds were assessed in a reduced fraction of their genome. Additionally, DNA methylation in the same fraction of the genome was measured in the sperm of RJF individuals to identify possible correlations with the mutations found between RJF and the domesticated breeds. Our study shows that although the vast majority of CpG-related mutations found relate to CNVs, CpGs disproportionally associate to SNPs in comparison to CNVs, where they are indeed substantially under-represented. Moreover, CpGs seem to be hotspots of mutations related to speciation. We suggest that, on the one hand, CpG-related mutations in CNV regions would promote genomic ‘flexibility’ in evolution, i.e., the ability of the genome to expand its functional possibilities; on the other hand, CpG-related mutations in SNPs would relate to genomic ‘specificity’ in evolution, thus, representing mutations that would associate with phenotypic traits relevant for speciation.